Microstructure Features and Degradation Mechanisms of Low-Pressure Evaporator Tube Steels in Combined Cycle Power Plants - Nugraha, YangYang Gilang; Erwin, Erwin; Listijorini, Erny; Dwinanto, Dwinanto; Alhamidi, Ahmad Ali; Satria, Dhimas; Saefuloh, Iman; Yusuf, Yusvardi; Sunardi, Sunardi (Universitas Sultan Ageng Tirtayasa, 2024)
A leakage failure occurred in a low-pressure evaporator tube of a Heat Recovery Steam Generator (HRSG) in a combined cycle power plant. The failed tube, manufactured from ST 37.8 CL1 steel, was investigated to determine the root cause of failure. The analysis included visual inspection, metallographic examination, and hardness testing. Visual observation revealed localized leakage regions associated with material degradation. Metallographic analysis showed a ferrite–pearlite microstructure with pronounced pearlite growth and the presence of micro-cavities concentrated along grain boundaries. Hardness measurements indicated that the failed tube exhibited higher hardness values (average 83.3 HRB) compared to unused material (average 76.6 HRB), reflecting microstructural evolution during service. The tube operated at approximately 143.8 °C under continuous internal pressure. Long-term exposure to these conditions promoted creep damage, characterized by the nucleation of micro-cavities at ferrite–pearlite interfaces. Progressive cavity growth and coalescence reduced ductility and facilitated crack initiation, ultimately leading to leakage. The findings demonstrate that creep-induced cavity formation associated with pearlite growth was the primary failure mechanism of the low-pressure evaporator tube.